Preliminary Examination in the Process of Filing a Bankruptcy Case (Comparison of Hong Kong with Indonesia) - Gatot Hadi Purwanto; Cristovao Adao Da Silva (RechtIdee, 2025)
Each country has different mechanisms and requirements for filing bankruptcy cases against debtors. Indonesia, through Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, sets relatively simple requirements: the presence of two or more creditors and the failure to pay a debt that is due and collectible. However, this system does not recognize a preliminary examination mechanism to assess whether the debtor is truly insolvent or still solvent. This condition differs from the legal system in Hong Kong, which adheres to the common law tradition, where before a bankruptcy case is submitted to court, a preliminary examination is first conducted through the statutory demand mechanism. Creditors are required to file a legal demand against the debtor to pay the debt within 21 days. If the debtor can prove to the court that they are still solvent, the statutory demand can be rejected, preventing the bankruptcy petition from proceeding to trial.